(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2021)
The present article of investigation has as objective to analyze the present situation that crosses the small companies of transport of heavy load of containers in Guayaquil, for that it is due to mention that this is a very important activity in the commercialization of goods of national and international form, in such sense to obtain the objective of the investigation methods of qualitative and quantitative analysis were developed that allowed to collect the information that evidences the necessities by which the companies study go through. The results show that, despite the existence of a regulatory legislation, this promotes unfair competition, so, provoke the direct affectation of small businesses providing the service on the market.Finally, the loss of competitiveness towards large companies that set tariffs at convenience, in addition to the economic affectation produced by informal companies, is demostrated.